Who Gets Compartment Syndrome?: A Retrospective Analysis of the National and Local Incidence of Compartment Syndrome in Patients With Supracondylar Humerus Fractures. Issue 5 (May 2018) - Robertson, Alysia K.; Snow, Erica; Browne, Theodora S.; Brownell, Sha'Tia; Inneh, Ifeoma; Hill, Jaclyn F.
Abstract : Purpose: Although acute compartment syndrome (ACS) is associated with pediatric supracondylar humerus (SCH) fractures, there are limited data describing its incidence and risk factors. The purpose of our study was to report the local and national incidence of ACS with SCH and floating elbow (concomitant SCH and forearm) fracture patterns and the associated risk factors. Methods: We retrospectively queried data for SCH fracture patients over a 4-year period from our institution (a level I pediatric trauma center) and the National Trauma Data Bank (NTDB). Data on demographics, mechanism of injury, open versus closed fracture, length of stay, presence or absence of forearm fractures, and incidence of traumatic compartment syndrome were analyzed. The student t and χ 2 tests were utilized for group comparisons of continuous and categorical variables, respectively. Logistic regression was used to identify risk factors for compartment syndrome. Results are summarized as means with SD or odds ratios (OR) with 95% confidence intervals (CI). Statistical significance was set at P <0.05. Results: At our institution, 839 patients with SCH fractures met inclusion criteria. In total, 814 (97.02%) patients (average age, 5.96±2.58 y) sustained isolated SCH fractures during the indicated timeframe. SCH fractures with an associated forearm fracture were identified in 25 (2.98%) patients (average age, 7.00±3.03 y). Three patients (0.36%) with isolated SCH fractures were observed to have compartment syndrome. No compartment syndromes were identified in the patients with floating elbows. Within the same time period, the NTDB identified 31, 234 SCH fractures met inclusion criteria. Of those, 31, 167 patients had isolated SCH fractures (average age, 5.5±2.7 y). In total, 67 of the SCH patients (0.2%, P <0.0001) had documented ACS (average age, 7.3±3.5 y). The NTDB identified 1565 patients with floating elbows, including 13 (0.8%, P ⩽0.0001) who developed compartment syndrome (average age, 6.47±2.71 y). The NTDB query also identified 530 patients with neurovascular injury (NVI), with 4.5% (n=24) that developed compartment syndrome. In the regression analysis, older age (OR, 1.1; 95% CI, 1.0-1.2; P <0.0092), male sex (OR, 2.7; 95% CI, 1.5-4.8; P =0.0005), floating elbow fracture pattern (OR, 3.2; 95% CI, 1.7-6.1; P =0.0003) and NVI (OR, 25.0; 95% CI, 14.6-42.8; P ⩽0.0001) were identified as risk factors for developing compartment syndrome. Conclusions: Data from our institution and NTDB reveal that acute traumatic compartment syndrome is rare, occurring in ∼2 to 3 fractures of 1000. However, there is a significantly increased risk with NVI, floating elbow fractures, males, and older patients. Significance: Characterizing the incidence and associated risk factors of ACS with concomitant SCH and forearm fracture patterns can improve clinical understanding and management of pediatric patients.